EMBODIMENT OF REGIONAL CULTURAL RESILIENCE THROUGH PRESERVATION OF TRADITIONS: A STUDY ON THE TUMPENG SEWU TRADITION IN KEMIREN VILLAGE, BANYUWANGI REGENCY - Danugroho, Agus; Murtinigsih, Siti; Fitriasari, Paramitha Dyah (UI Scholars Hub, 2023)
This study aims to find out how the preservation of the Tumpeng Sewu Tradition in Kemiren Village, Banyuwangi Regency, has direct implications for regional cultural resilience. The preservation of the Tumpeng Sewu tradition in Kemiren Village, Banyuwangi Regency, is an interesting phenomenon because it has various impacts. In the midst of a global era that demands modernization, the preservation of traditions is very necessary so that they remain sustainable. However, it is also at risk of losing its local culture as a result of modernization. This is a descriptive qualitative study. The findings of this study suggest that the preservation of the Tumpeng Sewu Tradition, which employs cultural commodification, has the potential to contribute to and have an impact on a variety of sectors, particularly tourism in Banyuwangi Regency. The preservation of the Tumpeng Sewu Tradition in Kemiren Village has direct implications for regional cultural resilience. The findings of field researchers include several aspects, such as the socio-economic and daily behaviors of people who are influential as a result of the preservation of the Tumpeng Sewu Tradition in Kemiren Village.